Four new species of the spider genus Leclercera Deeleman-Reinhold (Araneae, Ochyroceratidae) from Nepal - Xu, Mingjie; Li, Fengyuan; Li, Shuqiang (Zootaxa, 2018)
Four new species of the spider genus Leclercera Deeleman-Reinhold, 1995 from the spider family Ochyroceratidae Fage, 1912 are described from Nepal: L. nagarjunensis Li et Li sp. nov., L. niuqu Li et Li sp. nov. (male only), L. sidai Li et Li sp. nov. and L. zhaoi Li et Li sp. nov. Leclercera mulcatus (Brignoli, 1973) comb.n. is transferred from the genus Psiloderces Simon, 1892. All new species were collected in leaf litter of moist forests, often close to the streams or lakes, which suggest an ecological preference for moist environments. A taxonomic identification key for male Leclercera is provided. Types of all new species are deposited in the Institute of Zoology, Chinese Academy of Sciences (IZCAS-Ar 34327–34339) in Beijing, China.